PEMBELAJARAN KOSA KATA BAHASA ASING BERBASIS TPR (TOTAL PHYSICAL RESPONSE) - Tri Mulyani wahyuningsih; Pipiet Furisari; Sri Oemiati (Bajang Institute, 2023)
Learning foreign languages ​​in early childhood requires certain strategies so that learning languages ​​feels fun so that they can motivate students to learn foreign languages. The purpose of this activity is to help improve the competence of teachers who are members of the RA/BA KKG throughout the Sambi sub-district in developing teaching methods for teaching foreign language vocabulary to early childhood. One of the methods introduced to teachers is TPR (Total Physical Response) based learning which is a language teaching method based on commands, speech, and motion. This activity was attended by 30 TK/RA teachers from the Sambi sub-district. The stages carried out in this activity are as follows 1) presentation of TPR-based teaching method material via powerpoint, 2) Introduction of teaching instruments or media to be used, 3) Practical teaching using the TPR method, 4) question and answer discussion. The results of this activity are KKG teachers RA/BA in Sambi sub-district can practice teaching foreign languages ​​well using TPR-based methods